Amyand's hernia: a finding in the diagnosis of inguinal hernia - Rodriguez, Mayra Cristina Castro; Ordaz, David Eduardo Torres; Lugo, Leonel Lozano; Romero, José Alfonso Martínez; Montes, José Ignacio Diego Pérez; Ortiz, Daniela Garcia (International Journal of Research in Medical Sciences, 2025)
Amyand's hernia is defined as the presence of a cecal appendix in the context of an inguinal hernia sac, which may be found with or without signs of aggravation. Since the very beginning in the medical history its defined as a rare entity, the epidemiology and outcomes are diverse, since the pathophysiologic mechanism is not fully understood it should always be considered in conjunction with the presentation of a right inguinal hernia, the initial diagnostic methods do not represent a sufficient specificity to be suspected in all cases, but within the surgical findings either with data of exacerbation or not, it is recommended to evaluate the underlying cecal tissue. The final objective of this present case is to bring light about the complexity in the diagnosis and the outcome of late diagnosis in a comorbid based population, since is time dependent about diagnostic resources and clinical suspicion become the last and fundamental utility for the clinician.